A disease that is difficult to diagnose and treat: evaluation of 343 spondylodiscitis cases. Issue 11 (November 2021) - Kaya, Safak; Kaya, Sehmuz; Kavak, Seyhmus; Comoglu, Senol
Objective: Spondylodiscitis is an important clinical a problem requiring serious approaches. In this study, we sought to raise awareness by examining the epidemiology and laboratory, clinical, and radiological findings of spondylodiscitis, which sometimes has a delayed diagnosis and which can be difficult to treat. Methods: In total, 343 patients with spondylodiscitis were included in the study. Results: The patients were classified as having as pyogenic (n = 153, 44.6%), brucellar (n = 138, 40.2%), or tuberculous (n = 52, 15.2%) spondylodiscitis. Meanwhile, 281 patients underwent magnetic resonance imaging, 71 underwent computed tomography, and 17 underwent scintigraphy for diagnosis. The rates of involvement at more than two segments and paraspinal abscess were significantly higher in tuberculous spondylodiscitis. However, disc involvement was significantly more common in brucellar and pyogenic spondylodiscitis. Conclusion: The incidence of spondylodiscitis has increased substantially, especially in the young population. The invasive procedures and high rate of culture negativity make the diagnosis difficult. Therefore, clinical and radiological findings are useful in the diagnosis of spondylodiscitis. Despite the high rate of culture negativity, every effort should be made to identify the causative organism using invasive methods.